When Management Fails: Evolutionary Perspectives and Adaptive Frameworks for Responding to Water Problems - Moench, Marcus; Dixit, Ajaya (Water Nepal, 2009)
Their paper takes as its starting point in a growing skepticism that integrated management is an adequate -or in some cases/appropriate paradigm to address many water related problems. The paper highlights the conceptual and practical limitations of integrated water management and encourages exploration of alternatives. Keywords: water management Water Nepal Vol. 12, No. 1&2, 2006 Page: 143-205